FINDS OF MODIOLULA (BIVALVIA; MYTILIDAE) IN THE EOCENE OF UKRAINE - Bielokrys L.S. (My University, 2001)
The shells of Modiolula parca sp. nov. are described from the Middle-Upper Eocene deposits of the Ukraine. Representatives of the genus are found in the Paleogene for the first time.
Keywords: Eocene; Modiolula; Ukraine; Cenozoic::Paleogene::Eocene; Кайнозой::Палеоген::Эоцен